Improving the Capabilities of Strategic Competence and Mathematical Disposition Using the Inquiri Model of Alberta Method - Supiyanto Supiyanto; Heris Hendriana; Rippi Maya (IKIP Siliwangi, 2018)
This study aims to improve the ability of strategic competence and mathematical disposition in mathematical learning using inquiry method of alberta model and correlation between the two. The subjects of this study are students of SMP class VII as many as two classes with a total of 70 students. The instruments used in data collection are written test of description for strategic competence and mathematical disposition and alberta model inquiry method. The research used a quasi experiment. Data on strategic competence and mathematical disposition were analyzed using Mann Whitney nonparametric tests. The results of this study are: (1) Improvement of students' strategic competency skills whose learning method using Inquiry Model Alberta is better than the usual method; (2) The mathematical disposition of students whose learning method using the Inquiry Model Alberta is better than the usual method; (3) There is a correlation between the ability of strategic competence with mathematical disposition of students whose learning method using Inquiry Model Alberta